In vitro antimicrobial activity of CatDex against Porphyromonas endodontalis - Carrillo-Sosa, María Fernanda Mayela; Rodríguez Delgado, Idalia; Flores Treviño, Jorge Jaime; De la Garza Ramos, Myriam Angélica; Madla Cruz, Elizabeth; Escamilla García, Erandi; Cárdenas Estrada, Eloy (Academic Journals, 2018)
An achievable goal in root canal therapy is to reduce the bacterial population to the lowest level. Irrigation and instrumentation play an important role in achieving this objective. Sodium hypochlorite (NaClO) is the most frequently used irrigation solution; however, its main disadvantage is cytoxic to soft tissues following inadvertent extrusion. CatDex is a substance that promises to match the antimicrobial effect of NaClO without being toxic. The aim of the study is to evaluate the in vitro antimicrobial activity of CatDex in doses ranging from 0.17 to 0.05% and compared it with NaClO 5.25, 2.5 and 1.25%, against Porphyromonas endodontalis. P. endodontalis sensitivity to NaClO and CatDex were performed using the disk diffusion method and the minimum inhibitory concentration (MIC). The percentage of P. endodontalis inhibition were 97.8% at 5.25% NaClO and 55% at 0.145% CatDex. CatDex could be considered as a possible alternative for irrigation in root canal therapy. However, more studies are needed to verify its effect and to determine its correct clinical use.